2017
DOI: 10.2108/zs160194
|View full text |Cite
|
Sign up to set email alerts
|

Low Genetic Variation of Red-Crowned Cranes on Hokkaido Island, Japan, Over the Hundred Years

Abstract: The red-crowned crane (Grus japonensis) is recognized internationally as an endangered species. Migratory populations breed in eastern Russia and northeastern China, whereas the resident population inhabits the island of Hokkaido, Japan. Although the population inhabiting Hokkaido had experienced a severe bottleneck by the end of the 19th century, the population size has recovered to about 1500 and continues to increase now thanks to conservation efforts. A previous study reported that no marked genetic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 14 publications
(30 reference statements)
2
18
1
Order By: Relevance
“…Although the genetic markers used were different, notable differences in these heterozygosity indexes are additional evidence for scarce genetic diversity in the island population. Low genetic diversity in the island population has been frequently reported based on haplotype analysis [ 9 , 10 , 27 ] and microsatellite analysis [ 17 , 18 ]. It has been assumed that there was a high degree of inbreeding or genetic drift as the cause of scarce diversity in the island population [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the genetic markers used were different, notable differences in these heterozygosity indexes are additional evidence for scarce genetic diversity in the island population. Low genetic diversity in the island population has been frequently reported based on haplotype analysis [ 9 , 10 , 27 ] and microsatellite analysis [ 17 , 18 ]. It has been assumed that there was a high degree of inbreeding or genetic drift as the cause of scarce diversity in the island population [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low genetic diversity in the island population has been frequently reported based on haplotype analysis [ 9 , 10 , 27 ] and microsatellite analysis [ 17 , 18 ]. It has been assumed that there was a high degree of inbreeding or genetic drift as the cause of scarce diversity in the island population [ 10 ]. In this study, the average of FIS of the 11 InDel markers as an inbreeding index was 0.095.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autopsy results showed that 3K1 died of eating seeds mixed with pesticide, which is a common form of poisoning reported (Zhou et al 2014). The sedentary Red-crowned Crane population is stable but with low genetic variation (Harris and Mirande 2013; Akiyama et al 2017). Researchers found that if migratory behavior was completely dominated by genetic factors, it was likely to persist, regardless of population size; however, for species relying mainly on learning for their first migration, small migratory populations may face strong "Allee effect (individual fitness tends to decline at low population density)'', which will ultimately lead to loss of migratory behavior (Stephens and Sutherland.…”
Section: Discussionmentioning
confidence: 99%